Women Agrarian Entrepreneurs and Gender Inequality in the Chilean Rural Sector After Independence from Spain, 1830s-1860s - Nazer-Ahumada, J; Navarrete-Montalvo, J; Llorca-Jana, M; Araya-Valenzuela, R (Pontificia Universidad Catolica de Chile, 2020)
We provide the first estimates of gender income and land inequality in Chile during the first decades after independence, when Chile was a predominantly agrarian society. We have used a new source: the records of the first agricultural censuses ever made for any Latin American republic. We found that there were over six times more male landowners than women, and that male owners gathered up to 87% of total agricultural income (of those paying the catastro). On the positive side, we found that female landownership was more widespread than has previously been assumed by Chilean historians, although it was declining in relative terms. We have also identified the main elite women agrarian entrepreneurs, finding that one of the biggest landowners of this period was a woman, who has been ignored in the historiography. We have documented her economic activities, as well as those of many other prominent women agricultural entrepreneurs, thus showing that women s involvement in crucial entrepreneurship activities started earlier than previously been acknowledged, from colonial times. © 2020, Pontificia Universidad Catolica de Chile.